Relationships among Islamic Work Ethics, Knowledge Sharing Behaviors and Innovative Work Behaviors: Mediating effects of Work Engagement - Wasif Ali; Asif Niaz; Muhammad Ali (Pakistan Journal of Islamic Research)
Religion is the most important social institutions that are capable related with individuals’ attitude, characteristics, and behaviors. The Islamic Work Ethics (IWE) is a rising thought in the arena of organizational behavior. The workplace and religious convictions and Islamic values influence the different attitudes and behaviors of individuals in organizations. The study plan to explore the direct influence of IWE on knowledge sharing behaviors (KSB) and innovative work behaviors (IWBs) among employees; and indirect effect via work engagement (WE). The data were collected by self-administered questionnaire form 308 employees of Islamic banking sector working at Lahore through convenience sampling technique. Structural equation modeling (SEM) was utilized for hypotheses testing. Findings suggest that IWE increases WE, KSB, and IWB among employees. In other words, employees having high IWE are more engaged with work, sharing knowledge, and exhibit innovative behaviors in the organizations. This study provided initial empirical evidence regarding the intervening role of WE among IWE and IWB and KSB. The implications, limitations and future directions are likewise discussed.